Suppression of Hyperpolarization-Activated Cyclic Nucleotide-Gated Channel Function in Thalamocortical Neurons Prevents Genetically Determined and Pharmacologically Induced Absence Seizures - (:unkn) unknown (SOC NEUROSCIENCE, 2018)
Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels and the I-h current they generate contribute to the pathophysiological mechanisms of absence seizures (ASs), but their precise role in neocortical and thalamic neuronal populations, the main components of the network underlying AS generation, remains controversial. In diverse genetic AS models, I-h amplitude is smaller in neocortical neurons and either larger or unchanged in thalamocortical (TC) neurons compared with nonepileptic strains. A lower expression of neocortical HCN subtype 1 channels is present in genetic AS-prone rats, and HCN subtype 2 knock-out mice exhibit ASs. Furthermore, whereas many studies have characterized I-h contribution to absence-like paroxysmal activity in vitro, no data are available on the specific role of cortical and thalamic HCN channels in behavioral seizures. Here, we show that the pharmacological block of HCN channels with the antagonist ZD7288 applied via reverse microdialysis in the ventrobasal thalamus (VB) of freely moving male Genetic Absence Epilepsy Rats from Strasbourg decreases TC neuron firing and abolishes spontaneous ASs. A similar effect is observed on gamma-hydroxybutyric acid-elicited ASs in normal male Wistar rats. Moreover, thalamic knockdown of HCN channels via virally delivered shRNA into the VB of male Stargazer mice, another genetic AS model, decreases spontaneous ASs and I-h-dependent electrophysiological properties of VB TC neurons. These findings provide the first evidence that block of TC neuron HCN channels prevents ASs and suggest that any potential anti-absence therapy that targets HCN channels should carefully consider the opposite role for cortical and thalamic I-h in the modulation of absence seizures.
Keywords: absence epilepsy; channelopathy; HCN channels; thalamocortical rhythms; thalamus; CORTICAL PYRAMIDAL NEURONS; I-H; SYNAPTIC-TRANSMISSION; REVERSE MICRODIALYSIS; NETWORK MECHANISMS; THALAMIC NEURONS; WAVE DISCHARGES; EXCITABILITY; SIRNA; EPILEPSY